Prolactin rescues and primes autoreactive B cells directly and indirectly through dendritic cells in B6.Sle3 mice. (10th April 2013) - Gonzalez, J.; Saha, S.; Peeva, E.
Summary The lupus susceptibility interval Sle3/5 confers responsiveness to prolactin in C57BL/6 (B6) mice and hyperprolactinaemia induces a lupus‐like phenotype in B6.Sel3/5 mice. In this study, the immunostimulatory effects of prolactin in B6 mice containing the Sle3 portion of the Sel3/5 interval (B6.Sle3 mice) were dissected. Because of the Sle3 interval's involvement in activation of myeloid cells, the effect of dendritic cells (DCs) from prolactin‐treated B6.Sle3 mice on the phenotype of B6 mice was also evaluated. B cells from prolactin‐treated B6 and B6.Sle3 mice and from B6 recipients of prolactin‐modulated DCs from B6.Sle3 mice were tested for DNA‐reactivity and resistance to B cell receptor (BCR)‐mediated apoptosis. The expression of co‐stimulatory molecules on lymphocytes and myeloid cells was also evaluated. In prolactin‐treated B6.Sle3 mice, transitional type 2 B cells increased while type 1 B cells decreased as a consequence of prolactin‐induced resistance to BCR‐mediated apoptosis leading to the survival of DNA‐reactive B cells. Follicular B cells from prolactin‐treated mice expressed increased levels of CD40, B7·2 and IAb, and DCs and monocytes had higher levels of CD44 and B7·2 than placebo‐treated mice. Adoptive transfer of DCs from prolactin‐treated B6.Sle3 mice to B6 recipients demonstrated the intrinsic ability of prolactin‐modulated DCs to induce a development of lupus‐like characteristics in B6 mice. Based on these results, prolactin accelerates the breakdown of immune tolerance in B6.Sle3 mice by promoting the survival, maturation and activation of autoreactive B cells, DCs and macrophages.